Pelatihan Canva sebagai Alternatif Media Pembelajaran Digital Berbasis Paradigma Merdeka Belajar untuk Guru SD Negeri 1 Purwogondo - Muhafid, Ervian Arif; Solihah, Nining Ma’rifatus; Rahmawati, Widiyas; Azizah, Hanifah Nur; Niswah, Hulwatun; Rakhmat, Arif Nur (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
The development of information and communication technology has brought influence in various fields of life including in the field of education. For this reason, educators in the Kurikulum Merdeka are required to continue to be creative and innovative in making or looking for creative and interesting learning media references. The Canva training held at SD Negeri 1 Purwogondo aims to introduce and train teachers to be skilled in using the Canva platform to create learning media. There are 3 stages in this training, namely the preparation, implementation, and evaluation stages. The preparation phase was carried out in coordination with SD Negeri 1 Purwogondo. The implementation stage consists of 2 core activities, namely material presentation by resource persons and training as well as guidance on making learning media using Canva. After the training stage, it was continued by giving questionnaires to the participants as a form of evaluation. The implementation of Canva training activities went well and provided benefits for teachers. The content of the material is considered good and relevant, with a satisfaction level of 67%. The resource persons are considered to have a good understanding and are able to convey the material clearly which is shown in the results of the questionnaire with a percentage of 79% very good in delivering material and 61% of good answers in the discussion / question and answer session. However, there were some suggestions from participants regarding the lack of time allotted for material delivery and for discussion/question and answer.